PERAN MEDIA SOSIAL “FACEBOOK” JELANG PEMILIHAN UMUM KEPALA DAERAH TAHUN 2017 DI KABUPATEN ACEH JAYA - Aminah Aminah (SOURCE : Jurnal Ilmu Komunikasi, 2017)
This study aims to explain the role of Social Media "Facebook" and its impacts ahead of the elections of regional heads in 2017 in Aceh Jaya district. Data required in this study was obtained through literature and field research. The research literature is done by reading textbooks, legislation, and other reading materials related to this research. While the field research conducted by interviewing informants. The results showed that social media "Facebook" very effective way of delivering a variety of things including the introduction of a track record as well as the vision and mission of the future leaders of Aceh Jaya fore. Campaigns that use social networking "Facebook" more influential than campaigns that are only focused on the delivery of any information or content (in the sense of simply using billboard and his card only). In the use of social media "Facebook" there are various impacts. There are two impacts: the effect of positive and negative impacts. The positive impact of the using social media "Facebook" in the election of Aceh Jaya, namely (1) the establishment of kinship fellow Team (timses) of each candidate, (2) can foster public participation in politics (3) provides information on the dynamics of the election in Aceh Jaya (4) to introduce the candidates (5) to introduce the vision and mission of the candidates. As for the negative impact of (1) to attack each other between supporters and supporters Irfan TB Well yahGam (2) Dropping Party Opposition. Keywords: Role of Facebook, Political Communication and Election